Heterogeneous Quality Firms And Trade Costs - Helble, Matthias (The World Bank, 2008)
There is increasing empirical evidence that vertical product differentiation is an important determinant of international trade. However, the economic literature so far has solely focused on the case in which quality trade stems from differences between countries. No studies investigate the role of quality trade between similar economies. This paper first develops a simple theoretical trade model that includes vertical product differentiation in a heterogeneous-firm framework. The model yields three main predictions for trade between similar economies. First, exported goods are of higher quality than goods sold on the domestic market. Second, larger economies have on average higher export qualities compared with smaller economies. Third, with increasing trade costs higher quality goods are exchanged. For all three effects, strong empirical support is found using detailed export trade data of the United States and 15 European Union countries